Analisis Penggunaan Metode Altman Z-Score dan Springate untuk Mengetahui Potensi Terjadinya Financial Distress pada PT Ace Hardware Indonesia Tbk Periode 2019-2022 - Fadila, Leli; Nurhayati, Nurhayati (SEIKO : Journal of Management & Business, 2024)
In the business world, a company is formed with the aim of making a profit or profit. If there is a consecutive decline in profit, it will trigger financial distress, which is a condition where the company faces difficulties with financial problems. Therefore, it is important for a company to analyze the company's financial statements carefully and in-depth to find out the potential for bankruptcy for the company. By using bankruptcy prediction tools such as the Almant Z-Score and Springate S-Score methods. In this study, a type of secondary data is used in the form of corporate financial statements of PT ACE Hardware Tbk Indonesia for the 2019-2022 period which are listed on the Indonesia Stock Exchange (IDX). And using external data sources, namely from outside the company in the form of notes on company reports, documentation, book references and journals. The data collection method in this study uses the library research method through the data analysis method in the form of a quantitative descriptive analysis method.